Chicken Onion Ring (Allium Cepa L) With Tar-Tar Suace pada Majas Space & Resto Atb Bandung - A. Kholiq Muharman; Irsad Muhyiddin (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Onion rings are made from onion slices coated in breadcrumbs and fried, typically served with tartar sauce. Chicken onion rings are a variation that combines onion rings with a chicken batter that envelops the onions. The chicken batter is made from ground chicken breast fillet mixed with tapioca flour as a binder and various spices to impart a distinctive flavor. This research aims to determine the panelists' level of preference for the organoleptic test, which includes appearance, aroma, color, texture, and taste, as well as standard recipes and business analysis. The research method employed is research and development. The study results reveal the standard recipe for making Chicken Onion Rings with Tartar Sauce, consisting of the following ingredients: 250g chicken breast fillet, 50g tapioca flour, 2 onions, 50g all-purpose flour, 250g breadcrumbs, 2 eggs, 500ml cooking oil, 5g salt, 10g chicken powder, 15g MSG, 3g ground pepper, 100g mayonnaise, 20g gherkin, and 50ml water. The evaluation criteria indicate that for appearance, 92% (very much liked) and 8% (liked); for color, 96% (very much liked) and 4% (liked); for aroma, 84% (very much liked) and 16% (liked); for texture, 88% (very much liked) and 12% (liked); and for taste, 92% (very much liked) and 8% (liked). Based on the business analysis of the Chicken Onion Rings with Tartar Sauce, the following conclusions can be drawn: food cost is Rp8,778, and selling price is Rp22,000. The product will break even after selling 151 portions. To achieve a target margin of Rp3,000,000 per month, the author must sell 378 portions per month. The author takes a profit of 40% from sales.